Acetone absorption in UV‐irradiated polycarbonate. Issue 7 (26th July 2017) - Hsiao, Yu Chun; Harmon, Julie P; Chuang, Yu‐Fan; Chiang, Donyau; Lee, Sanboh
Abstract : Isothermal acetone absorption in UV‐irradiated polycarbonate (PC) was investigated at temperatures from −23 to +25°C. The crystalline fraction of PC increased with UV dose. The anomalous transport data were analyzed based on Harmon's model which includes contributions from Case I transport characterized by the diffusion coefficient, D, and Case II transport characterized the velocity, v . Diffusion coefficients were monitored by both mass uptake using the model ( D and v ), and movement of the sharp front ( D f ). Plots of log of D, v, and equilibrium swelling ratio (ESR) versus 1/ T exhibited similar features. That is, plots were linear and superimposable for all doses at the higher temperatures, and exhibited a transition temperature and then a linear region that varied with dose. The values of D, D f, and v increased with increasing dose, whereas the ESR decreased with dose. The direction of Case II transport was opposite to that of Case I diffusion during which time, sorbed solvent was expelled from the samples. Results are discussed in terms of a solvent‐induced change in lattice structure at the lower temperatures and in terms of UV radiation effects on the PC matrix that enhance solvent crystallization. POLYM. ENG. SCI., 58:1174–1183, 2018. © 2017 Society of Plastics Engineers